2017
DOI: 10.1039/c7cp02570j
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylsilyl hedgehogs – a novel class of super-efficient hydrocarbon surfactants

Abstract: Presented here are the results for a novel class of hydrocarbon surfactants, termed trimethylsilyl hedgehogs (TMS-hedgehogs), due to the presence of silicon in the tails. By comparing the surface properties of these hybrid hedgehogs to purely hydrocarbon equivalents, links between performance and the structure are made. Namely, by controlling the molecular volume of the surfactant fragments, improvements can be made in surface coverage, generating lower surface energy monolayers. Small-angle neutron scattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 40 publications
(35 reference statements)
0
33
0
Order By: Relevance
“…One of the clearest ways of characterizing an adsorbed layer is in terms of its limiting area per molecule Amin, or area per molecule at the CMC, as this provides an indication about how the molecular structure controls packing at the interface. 29 As has been previously reported, 43 it is instructive to both compare and investigate how the tail branching, and hence surfactant tail density, leads to the observed interfacial properties.…”
Section: Surface Tension Lowering Ability Of Double Tail and Triple Tail Surfactantsmentioning
confidence: 83%
See 2 more Smart Citations
“…One of the clearest ways of characterizing an adsorbed layer is in terms of its limiting area per molecule Amin, or area per molecule at the CMC, as this provides an indication about how the molecular structure controls packing at the interface. 29 As has been previously reported, 43 it is instructive to both compare and investigate how the tail branching, and hence surfactant tail density, leads to the observed interfacial properties.…”
Section: Surface Tension Lowering Ability Of Double Tail and Triple Tail Surfactantsmentioning
confidence: 83%
“…The reason for this being due to the larger atomic radius of Si compared to C which allows for a lowering of the packing density per unit area. 29 The Amin values for the range of TMS surfactants studied by Czajka et al were found to decrease with increasing number of CH2 groups, therefore showing that the molecules are able to pack more efficiently at the air/water interface. 29 This behaviour has been previously understood due to a decrease in the rigidity of the surfactant tail as the length is increased; a behaviour that is also observed when comparing AOT14 to AOTtBE in Table 2.…”
Section: Links Between Lowering Surface Tension and Surfactant Tail Densitymentioning
confidence: 93%
See 1 more Smart Citation
“…In earlier studies, surfactants having TMS-terminated tails were found to generate very low surface energies (surface tensions), and comparable to short fluorocarbons in water (the limiting aqueous surface tension is 22.8 mN/m for the double TMS-chain terminated surfactant AOTSiC) [39]. As an example application of low surface energy surfactants, superspreading of aqueous solution on polyvinylidene difluoride (PVDF) surface was demonstrated by using the TMS surfactant [40,41].…”
Section: Figure 1 Structures Of Thiophene Monomers Having Trimethylsi...mentioning
confidence: 99%
“…It is not too surprising that the molecular structure of siloxane groups (hydrophobic tails) has a major effect on their physiochemical properties, such as the CMC, the surface tension at the CMC ( γ CMC ), the maximum excess surface concentration (Γ max ), and the area occupied by a single cationic silicone surfactant molecule at the air/water interface ( A min ). In recent years, considerable effort has been invested in the design and synthesis of permethylated silicone surfactants to study the relationship between the molecular structure and aggregation behavior in aqueous solution (Czajka et al, ; Hao et al, ; Qin et al, ; Tan et al, ). It should be noted that most nonionic silicone surfactants are prepared by hydrosilylation between hydrosilane and allyl‐terminated hydrophilic chains using an expensive platinum catalyst, which can result in two regioisomers.…”
Section: Introductionmentioning
confidence: 99%